Sanksi Pidana terhadap Kecelakaan yang Menyebabkan Matinya Orang di Perlintasan Sebidang Rel Kereta Api yang tidak Memiliki Palang - Muhammad Taufiq; Wicaksono Putra Hariyadi; Angga Saputra (Universitas Batanghari Jambi, 2026)
Road users must give trains precedence at level crossings between railway lines and highways, according to Law Number 23 of 2007 concerning Railways, Article 124. This implies that at certain level crossings, train drivers must prioritize trains. However, in practice, many level crossings lack safety barriers, increasing the likelihood of train accidents. The high number of accidents near railway crossings is also caused by various other reasons. The research methodology of this journal is normative. To understand, clarify, and assess legal concepts or principles, normative scholars examine legal documents, regulations and provisions, court decisions, legal theories, and legal literature. Train drivers who make mistakes, whether intentional or not, are subject to criminal sanctions as outlined in Article 361 of the Criminal Code, Article 358 of the Criminal Code, and Article 360 of the Criminal Code.